Tindak Tutur Direktif dan Komisif Pedagang dan Pembeli di Pasar Kebun Kelapa Kecamatan Beringin Kabupaten Deli Serdang - Desi Trisanti Desi; Rosmilan Pulungan (Medan Resource Center, 2022)
The purpose of this study was to analyze directive speech acts in the interaction of traders and buyers at the Kebun Kelapa market, Beringin sub-district, Deli Serdang district. This study used descriptive qualitative method. Research data collection was carried out using a listening technique using the help of recording equipment and notes as well as interviewing buyers and traders. There are six types of directive speech acts used in the speech of traders and buyers, namely 39 types of question speech acts, 15 requests speech acts, 6 permission speech acts, 2 prohibited speech acts, 1 advice speech acts, and 1 speech acts. command 5. The most common type of directive speech act found is the type of question speech act. The speech act of questioning is most widely used by both the buyer and the seller to ask for prices, types of goods, models, and others. There are four types of commissive speech acts used in the utterances of buyers and sellers, namely the speech act of offering as many as 12, swearing speech acts 1, promising speech acts 4, and vowing speech acts 1